Study on mechanical behaviours of rail fasteners and effects on seismic performance of urban rail viaduct. (October 2021) - Huang, Yong; Wang, Junjie; Le, Weijie; Zhang, Liang; Su, Junsheng
Abstract: The mechanical properties of rail fasteners play a key role in rail-structure interaction of urban rail viaduct. To reduce vibration and noise, the damping materials such as rubber cushion pads are used as the assemble parts of the rail fasteners in urban rail viaduct. The use of the damping materials causes the mechanical behaviours of rail fasteners to be different from the traditional ones whose longitudinal stiffness can be simplified as linear elastic, elastic–plastic or bilinear models. It is important to capture the mechanical behaviours of the rail fastener for accurately predicting the nonlinear seismic response of urban rail viaduct. In this paper, the quasi-static and dynamic cyclic tests of three kinds of commonly used rail fasteners (Type WJ-2A, Type DTIII2, and Type ZX-3) in China urban rail transit were conducted to explore the mechanical behaviours of rail fasteners. On this basis, the Hardin-Drnevich model is used to simulate the nonlinear behaviours of rail fasteners. Analysis results showed that the Hardin-Drnevich model could describe the quasi-static and dynamic cyclic response of Type WJ-2A and Type DTIII2 rail fasteners with reasonable accuracy, while its prediction accuracy for Type ZX-3 rail fasteners are relatively lower than others. Moreover, the Hardin-Drnevich model can predict the nonlinear dynamic response of Type WJ-2A fastener under earthquake loading very well. The calibrated parameters of Hardin-Drnevich model were used to the rail fasteners in the nonlinear seismic response analysis of the practical urban rail viaduct, and that were compared with that using idealized elastic–plastic model of the rail fastener. Comparison results demonstrated that, the mechanical constitutive relations of the rail fastener have obvious effects on the seismic performance of rail viaduct, and the effects are more distinct in the longitudinal direction than in the transversal direction.